Risk or Return? The Effect of Face Consciousness Influences on the Career Construction of Chinese Rural Dwellers in Urban Areas - Tang, Mingfeng; Li, Fenglian; Miesing, Paul; Mei, Mei; Xu, Peng (Frontiers in Psychology, 2022)
This research improves our understanding of entrepreneurial intention in the Chinese cultural context. Drawing on career construction theory, we received 408 valid surveys from rural Chinese dwellers and examined the relationships rural Chinese have among “face consciousness,” indecisiveness, career adaptability, and entrepreneurial intention. We found that those who are fearful of losing face are less likely to have entrepreneurial intentions, but one’s desire to gain face has no significant direct impact on entrepreneurial intention. In addition, face consciousness and an indecisive personality interact to influence career adaptability and, in turn, entrepreneurial intention. In sum, this study supports the career construction perspective in understanding the formation of entrepreneurial intention and offers theoretical, practical, and policy implications for entrepreneurial career counseling and training.